GIS BASED LOSS ESTIMATION MODELING FOR FLOODING IN THE CASE OF LONG WAVE AS TSUNAMI - Lan, Nguyen Hong; Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2009)
This paper presents a GIS basedflood loss estimation modeling approach. Ageneral overview ofsteps in the existingflood loss estimation methodology is given. The existing methodology is limited to a certain categories ofdirect flood damages, such as residential and Jwn-residential buildings and transport damage. Direct damage to infrastructures is estimated as a percentage ofother damage. This is an integrated approach combining a flood inundation simulation model and a loss estimation model. In the loss estimation modeling, direct flo od damages are categorized into three main groups, namely urban, rural and infrastructure damages. GIS is an integral component ofthis approach for pre and post-processing ofthe spatial input and outputs. Finally, a scheme ofthe methodology is described.